Simulacra Laptop (Post-modern Study of Virtual World Communication Laptop Users Among FISIP UNS Students) - Putri Dwi Adhitya (Trigin Publisher, 2022)
This research is a qualitative descriptive research. The informants in this research are the student of FISIP UNS as laptop users. The data collection techniques were conducted through in-depth interviews, observation of a role and documentation, whereas the sampling of research was conducted with a “purposive sampling” technique. The data analysis is interactive analysis includes data reduction, data display, and conclusion. The results showed that the virtual world of communication which was accessed by student of FISIP UNS as a laptop users are false or not real, they communicate and made a friendship in unreal space. In the social networking Facebook access the communication in the virtual world is one of popular internet accesses in the student of FISIP UNS as laptop users. In view of social side, social networking Facebook is very useful to establish relations of friendship, either new friends or old friends. In the social networking the communication of virtual world, they can fall out their feelings or share stories with friends on these social networks. In the other hand the social networking also open an opportunity business; develop a talent of writing and many others. Besides, there are the weakness of the existence of the virtual world of communication, ie: affectivities time experienced by students of FISIP UNS as a laptop users, and the virtual world crime experienced by some informants that are student of FISIP UNS as a laptop users . To minimize the virtual world crime.